"Government Is an Instrument in Their Hands": Jeanette Rankin on Progressive Technologies of Democracy. Issue 1 (2nd January 2017) - Koenig Richards, Cindy; McKean, Paul
ABSTRACT: Jeannette Rankin's 1917 address at Carnegie Hall is replete with metaphors of political machinery, systems, and technologies. We argue that the metaphor of political machinery is central to Rankin's definition and enactment of democratic power because it creates a cohesive vision of systemic change that combines equal suffrage with other progressive reforms. While scholars have noted Rankin's appeals to domestic ideology, the political-machinery metaphor cluster provides a broader justification for equal suffrage as a necessary part of a democratic system. Further, Rankin's deconstruction of the complexities of political machinery works to enact Rankin's political leadership as the first woman to serve in the United States Congress.